Quantitative risk assessment of human exposure to Bacillus cereus group associated with household refrigerated storage of pasteurised milk in India - Sarkar, Prabir K. (Indian Journal of Dairy Science, 2017)
A quantitative risk assessment model was developed using response surface methodology and Monte Carlo simulation to evaluate public health risks associated with the consumption of pasteurised milk contaminated with Bacillus cereus s.l. in district of Darjeeling, India. Thirty percent of the pasteurised milk samples stored in domestic refrigerators contained B. cereus with the level of contamination up to 5 log cfu/ml. The distribution of initial population of B. cereus in pasteurised milk ranged from 1.83 to 4.16 log cfu/ml with mean value of 3 log cfu/ml. The distribution of storage temperature in the refrigerators ranged from 3.54 ºC to 12.84 ºC with mean value of 8.2 ºC; the probability of temperature being ≤7 ºC was only 25%. The storage time for milk in domestic refrigerators ranged from 0.76 to 3.55 days with the mean of 2.16 days. After optimisation of the results considering initial population of B. cereus to be 3 log cfu/ml, it was found that B. cereus s.l. cell count can reach the threshold level (>4 log cfu/ml) after 47.51 h, 45.54 h, 41.59 h, 35.26 h, 25.31 h and 24 h at 7 ºC, 8 ºC, 9 ºC, 10 ºC, 11 ºC and 12-13 ºC, respectively. If milk is stored for more than 24 h in domestic refrigerators, the chance of consumers being exposed to high levels of B. cereus s.l. is more which can lead to foodborne illnesses. Thus, the analysis of conditions reflective of current scenario in India indicates a high risk associated with consumption of pasteurised milk.